PENGARUH MOTIVASI TERHADAP KINERJA PEGAWAI PADA KANTOR KEMENTERIAN AGAMA KABUPATEN OGAN KOMERING ULU - Darmanah, Darmanah; Sari Devi, Tika; Satria, Anton (JMBI (Journal of Marketing and Business Intelligence), 2024)
The Office of the Ministry of Religious Affairs of Ogan Komering Ulu Regency apparently has not been fully implemented, where many jobs have not been completed on time so that employee performance is less elective due to lack of motivation from the punpunan to its employees. The problem faced by the Office of the Ministry of Religious Affairs of Ogan Komering in achieving its goals is the still low performance of employees in carrying out tasks which may be caused by the lack of motivation from the leadership. In this study, the problem focuses on How does motivation affect the performance of employees at the Office of the Ministry of Religious Affairs of Ogan Komering Ulu Regency and aims to determine the effect of motivation on employee performance so that in taking further steps it can improve employee performance. The results of this study, motivation from the leadership has a very large influence on improving employee performance. The suggestion given is that in addition to having to play an active role in their work environment, leaders must also provide an understanding of how to work well to achieve a result and be able to carry out the responsibilities that have been assigned.